2017
DOI: 10.1007/s11104-017-3539-8
|View full text |Cite
|
Sign up to set email alerts
|

Nickel hyperaccumulation mechanisms: a review on the current state of knowledge

Abstract: Background Hyperaccumulator plants are unusual plants that accumulate particular metals or metalloids, such as nickel, zinc, cadmium and arsenic, in their living tissues to concentrations that are hundreds to thousands of times greater than what is normal for most plants. The hyperaccumulation phenomenon is rare (exhibited by less than 0.2% of all angiosperms), with most of the ~500 hyperaccumulator species known globally for nickel. Scope This review highlights the contemporary understanding of nickel hyperac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 82 publications
2
43
0
Order By: Relevance
“…Leaves and flowers from site 2 present no significant differences between them in terms of Ni accumulation, with 7723 and 7264 mg kg −1 , respectively. These results are expected, since other studies show that the leaves are the main storage organ where the majority of Ni is accumulated [38]. Groeber et al reported that flowers of hyperaccumulator plants can accumulate Ni concentrations as high as that in leaves, which is in agreement with this study [39].…”
Section: Plantssupporting
confidence: 92%
“…Leaves and flowers from site 2 present no significant differences between them in terms of Ni accumulation, with 7723 and 7264 mg kg −1 , respectively. These results are expected, since other studies show that the leaves are the main storage organ where the majority of Ni is accumulated [38]. Groeber et al reported that flowers of hyperaccumulator plants can accumulate Ni concentrations as high as that in leaves, which is in agreement with this study [39].…”
Section: Plantssupporting
confidence: 92%
“…All leaf samples showed increased Ni, Co, and Mn concentrations after 26 days of accumulation (>20%). Hence, leaves are likely the main storage organ for Ni, Co, and Mn hyperaccumulation [21]. Overall, a distinct trend for accumulation in plant tissues, especially for higher concentrations (18/27, green), and a reduced contamination of soils were observed (7/9, red).…”
Section: Contamination Groupmentioning
confidence: 93%
“…Images of the leaves at contamination levels 1 and 2 for Ni, Co, and Mn after the accumulation phase are shown in the supporting information ( Figure S4). The Ni uptake mechanism was studied intensively in recent years and the translocation can be described by multiple complexation and decomplexation steps (chelating agents like histidine, glutamine, and carboxylic acids) during the Ni 2+ transport from the roots via the xylem to the leaf [21]. In the leaf, Ni is generally complexed by citric acid and sequestered in leaf vacuoles via transporters from the zinc transporter protein (ZIP) family [21].…”
Section: Contamination Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out over the past 40 years have focused on Ni (hyper)accumulators (e.g. Jaffré et al, 1976;Lee et al, 1977;Brooks et al, 1979;Reeves et al, 1983) to better understand the Ni accumulation phenomenon resulting from the stimulated uptake of Ni by the roots and an efficient transfer of Ni to the leaves through efficient xylem transport and phloem distribution (Centofanti et al, 2013;Tang et al, 2016;Deng et al, 2018), and to evaluate their phytomining and phytoremediation potential (e.g. Minguzzi and Vergnano, 1948;Reeves et al, 1996Reeves et al, , 1999Puschenreiter et al, 2005;Centofanti et al, 2012;van der Ent et al, 2015).…”
Section: Introductionmentioning
confidence: 99%